Preliminary Evaluation of a Numerical System of Prediction for Surface Solar Irradiance and Cloudiness in a Site with a Subtropical Humid Climate - Gabriel Cazes Boezio (Atmosphere)
This study explores a prediction system for global horizontal irradiance and cloudiness in a humid subtropical terrestrial region. This system consists of regional simulations performed with the Weather Research and Forecasting model using the initial and boundary conditions from the Global Forecast System. The predictions show significant biases for the variable of interest, with notable variations within the daily and annual cycles. This study also finds significant biases in cloud incidence and clarity index predictions, with relevant diurnal and seasonal variations. During austral summer, multiplying the relative humidity of initial and boundary conditions by a fixed factor improves the forecasts of global horizontal irradiance and cloud incidence for the central hours of the day and the afternoon. During austral winter, an empirical correction of the clarity index obtained from the simulation’s outputs also shows the potential to improve the forecasts’ biases. This work proposes a hypothesis about the causes of the forecast biases.